Digital literacy model to improve the marketing skills of micro, small, and medium enterprises women with a community-based educational approach - Trisninawati Trisninawati; Dewi Sartika (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Women in Micro, Small, and Medium Enterprises (MSMEs) often need help marketing their products or services, including limited access to resources for promotion and distribution. Restricted accessibility and a lack of understanding of digital technology are significant barriers limiting their marketing potential. Digital literacy becomes a crucial element that can change the paradigm and open opportunities for women MSMEs to overcome these challenges. This study aims to understand the experiences and skills of women MSMEs in applying digital literacy and propose a community-based education model to enhance marketing capabilities. This study uses a qualitative approach with a case study method. A total of 15 informants from the MSME community members of the Indonesian Muslim Entrepreneurs Association (IPMI) Palembang were selected based on inclusion criteria, including experience in the MSME business, a minimum education level of high school, and active involvement in marketing activities. Data were collected through in-depth interviews with an interview guide covering themes of digital literacy and marketing skills. Most respondents have a low level of digital literacy and limitations in using digital technology for business. The main challenges faced are difficulties adapting to digital technology and concerns about digital security. Most respondents still rely on conventional marketing methods and feel less confident managing digital marketing campaigns. Digital literacy and marketing skills remain significant challenges for women MSMEs in Palembang. A community-based education model is needed to overcome these obstacles, including digital literacy workshops, mentor-mentee programs, experience-sharing sessions, and specific skills training.